Understanding key factors contributing to mental health challenges among pediatric nurses: a systematic review - Limungi, Godfrey Mbaabu; Amer, Mesmar; Elmadani, Mohammed; Simon, Klara; Hamad, Osama; Horvath, Eva; Livia, Patty; Orsolya, Mate (Frontiers in Public Health, 2025)
BackgroundThe mental health and wellbeing of nurses, particularly pediatric nurses, have garnered attention due to the increased risk of mental health challenges associated with their demanding profession. These nurses are especially vulnerable, yet their mental wellbeing is often understudied.ObjectiveThis systematic review aims to identify and analyze key factors associated with mental health challenges among pediatric nurses and explore how these factors interact to influence their wellbeing.MethodologyThe review protocol was registered in PROSPERO (CRD42024553062) and adhered to PRISMA guidelines. A comprehensive search was conducted across six databases: PubMed Scopus, CINAHL, Web of Science, Medline, and Embase. Eligible studies included both qualitative and quantitative studies that examined factors linked to mental health challenges among pediatric nurses. The quality of the studies was appraised using the Mixed Methods Appraisal Tool (MMAT). Data extraction and synthesis involved qualitative content analysis to identify key factors.ResultsFive studies from China, Turkey, Greece, Canada, and Saudi Arabia were included. The key factors identified were high workload, poor work environment, limited resources, and strained interpersonal relationships, lack of support, irregular shift patterns, demanding roles, and financial strain. These factors were significantly associated with increased stress, burnout, anxiety, and depression among pediatric nurses. The interaction of these factors created a complex web influencing their mental health, with supportive work environments and adequate financial compensation mitigating some negative effects.ConclusionThis systematic review identifies high workload, poor work environment, limited resources, and strained interpersonal relationships, lack of support, irregular shift patterns, demanding roles, and financial strain as key factors impacting the mental wellbeing of pediatric nurses. These factors interact to exacerbate stress, burnout, anxiety, and depression. Effective interventions should include manageable nurse-to-patient ratios, adequate resource allocation, fostering a supportive work culture, flexible scheduling, targeted support for senior nurses, and improved financial compensation.